2005
DOI: 10.1303/aez.2005.265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal doses of beta-cyfluthrin on mutant Drosophila melanogaster (Diptera: Drosophilidae)

Abstract: Laboratory experiment was conducted to examine sublethal effects of beta-cyfluthrin (Bulldock ® 025 SC) on the sepia mutant of Drosophila melanogaster at a temperature of 25Ϯ0.5°C, 50Ϯ5% relative humidity and a photoperiod of 16 : 8 (light : dark) hours. Males and females were exposed separately to beta-cyfluthrin (one tenth of the calculated LC 50 value) mixed in the diet for 24, 48 and 72 h. Fecundity, hatchability, pupation, adult emergence, larval, pupal and total developmental periods were evaluated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This indeed supports the claim that onion and garlic could serve as contraceptives in flies. Similar effects were observed in flies have also been reported (Nadda et al., 2005; Razdan et al., 2003).…”
Section: Discussionsupporting
confidence: 87%
“…This indeed supports the claim that onion and garlic could serve as contraceptives in flies. Similar effects were observed in flies have also been reported (Nadda et al., 2005; Razdan et al., 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Sublethal doses affect the physiological and behavioral properties of insects (Haynes 1988). Sublethal doses can influence the developmental time (Wang et al 2008), weight of larvae, pupae, adults (Yin et al 2008;Gupta and Chandel 1995), adult longevity (Cutler et al 2005;Ergin et al 2007), hatchability (Alyokhin et al 2008;Nadda et al 2005), fecundity (Haseeb and Amano 2002;Wang et al 2009), egg size (Fujiwara et al 2002;Yin et al 2008), and reproduction parameters such as the net reproductive rate (R 0 ), intrinsic rate of increase (r m ), finite rate of increase (k), generation time (T), doubling time (Dt) (Rezaei et al 2007;Zanuncio et al 2005;Lashkari et al 2007), and the sex ratio (Delpuech and Meyet 2003). Sublethal doses of insecticides frequently cause resurgence through physiological and ecological mechanisms (Ripper 1956;Luckey 1968).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the toxic effect in the F 1 generation was still present in the F 2 generation. A similar study analyzed the effect of a synthetic pyrethroid called beta-cyfluthrin on the sepia mutant of Drosophila melanogaster and concluded that it caused egg hatching to decrease (Nadda et al 2005). It is claimed that the reason for this may be inappropriate incorporation of the yolk, causing the embryo to fail to complete its phases of development.…”
Section: Resultsmentioning
confidence: 99%
“…It is claimed that the reason for this may be inappropriate incorporation of the yolk, causing the embryo to fail to complete its phases of development. Additionally, it has been suggested that a decrease in egg hatching may result from antifeedant and repellant effects of beta-cyfluthrin, leading to weak and nonviable egg laying (Nadda et al 2005).…”
Section: Resultsmentioning
confidence: 99%